1998
DOI: 10.14430/arctic1042
|View full text |Cite
|
Sign up to set email alerts
|

Transport of 137Cs And 239,240Pu with Ice-rafted Debris in the Arctic Ocean

Abstract: Ice rafting is the dominant mechanism responsible for the transport of fine-grained sediments from coastal zones to the deep Arctic Basin. Therefore, the drift of ice-rafted debris (IRD) could be a significant transport mechanism from the shelf to the deep basin for radionuclides originating from nuclear fuel cycle activities and released to coastal Arctic regions of the former Soviet Union.In this study, 28 samples of IRD collected from the Arctic ice pack during expeditions in 1989 -95 were analyzed for 137 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
17
0

Year Published

1998
1998
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(20 citation statements)
references
References 29 publications
2
17
0
Order By: Relevance
“…Most studies of ice-rafting in the Eurasia basin have also concentrated on the fine-grain fraction (Pfirman et al, 1989(Pfirman et al, , 1990Bischof, 1990;Nürnberg et al, 1994;Nørgaard-Pedersen, 1997;Landa et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Most studies of ice-rafting in the Eurasia basin have also concentrated on the fine-grain fraction (Pfirman et al, 1989(Pfirman et al, , 1990Bischof, 1990;Nürnberg et al, 1994;Nørgaard-Pedersen, 1997;Landa et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Dethleff et al, 1993;Nurnberg et al, 1994;Pfirman eẗ . al., 1997a,b;Landa et al, 1998 the Laptev and Kara Seas were identified as sources of potentially contaminated sea ice sediments. Entrainment of sediments into newly forming sea ice occurs during fall Ž .…”
Section: Transport Of River Contaminants By Arctic Seaicementioning
confidence: 99%
“…Cs burden in sea-ice sediments was found at varying sites in the central Arctic Ž Ocean Baskaran et al, 1996;Føyn and Svaeren, . 1997;Landa et al, 1998 . This relationship means that the more polluted fine fraction sea-ice sediments contain, the higher is their radionuclide burden, which underlines again the importance of fine-grained Arctic sea-ice sediments for contaminant transport.…”
Section: Radionuclide Datamentioning
confidence: 99%
“…PII: S 0 9 2 4 -7 9 6 3 9 9 0 0 0 8 8 -3 however, the total recent inventory of 1 PBq 137 Cs and 10 TBq 239,240 Pu may cause significant local and regional ecological problems in the case of a catastrophic -i.e., instantaneous -release. Different recent empirical and modeling studies focus on the pathways of man-made radionuclides with Arctic sea-ice and ocean water masses particu-Ž larly originated from the Kara Sea e.g., Pavlov and Pfirman, 1995;Harms, 1997a;Meese et al, 1997;Baxter et al, 1998;Krosshavn et al, 1998;Landa et . al., 1998;Mitchell et al, 1998 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation